2011
DOI: 10.1016/j.ejvs.2011.06.053
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Surveillance after Endovascular Aneurysm Repair in the UK

Abstract: Significant heterogeneity exists in surveillance after EVAR in the UK. Efforts should be made to establish consensus towards a national surveillance protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…Concerns with current practice include the diagnostic accuracy of different imaging modalities, patient attendance rates, interval presentations leading to reintervention, and nephrotoxicity and radiation exposure from CT. This uncertainty is reflected by wide variations in surveillance protocols used at different centres.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns with current practice include the diagnostic accuracy of different imaging modalities, patient attendance rates, interval presentations leading to reintervention, and nephrotoxicity and radiation exposure from CT. This uncertainty is reflected by wide variations in surveillance protocols used at different centres.…”
Section: Discussionmentioning
confidence: 99%
“…This study reflects long-term outcome at a single institution and may not be applicable to lower-volume endovascular practice 39 . Surveillance after EVAR remains heterogeneous 40 with the potential to confound comparisons of late endograft complications. As EVAR can be done with low mid-term aneurysm-related mortality, the improved prediction and detection of endograft complications, including sac expansion, should be the focus of further research.…”
Section: Discussionmentioning
confidence: 99%
“…23 This audit and previous research has shown heterogeneity in the incidence, detection rate and classification of the type of endoleak, 30 which may be due to differences in postoperative EVAR surveillance timing, the modality used, the technical capabilities of the chosen modality and the level of training and experience of the reporting practitioner. 3,30,31 In the context of hospital-based detection of abdominal aortic aneurysms (AAA) and the implementation of national AAA screening programmes, 32,33 the differences in postoperative EVAR surveillance practice may have international implications. It may lead to differences in cost-effectiveness, patient satisfaction and overall outcomes after EVAR.…”
Section: Detection and Classification Of The Type Of Endoleaksmentioning
confidence: 99%